Application of Bessel beams for ultrafast laser volume structuring of non transparent media - Alexeev, Ilya; Leitz, Karl-Heinz; Otto, Andreas; Schmidt, Michael (Physics Procedia, 2010)
The use of ultrashort laser pulses has been shown to be an attractive option for high quality micromachining. In these applications low energy laser pulses are tightly focused to achieve high light intensities. While this approach has been demonstrated to be successful, its application is challenged by the short Rayleigh range of a tightly focused laser beam. Precise positioning of material samples becomes crucial imposing extra requirements on sample flatness, tilt, and irregularities. To overcome some of these limitations an application of non-diffractive Bessel beams for laser material processing has been attempted recently. The non-diffractive focus of Bessel beams can have the depth of field significantly longer than the Rayleigh range of a Gaussian beam of a comparable diameter. With sub mJ laser pulse energy the light intensity along the line focus can reach and exceed the required threshold levels making laser Bessel beams suitable for material processing. Preliminary numerical simulations show that truncated by a micron size aperture Bessel beam still has the propagation depth sufficiently long to be suitable for volumetric micro structuring of non transparent media. The paper aims to demonstrate feasibility of ultrafast laser structuring of non transparent media using Bessel beam focusing geometry.
Created from Fastlane, Scopus look-up
Keywords: Bessel laser beams; Micro structuring; Ultrafast material processing

Application of Gaussian optical tweezers for ultrafast laser assisted direct-write nanostructuring - Quentin, Ulf-Hermann; Leitz, Karl-Heinz; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2012)
The minimal size of optically generated structures is always affected by diffraction. This fundamental limitation does not allow laser radiation to be focussed much smaller than half of its wavelength and therefore it also limits minimal feature sizes of laser produced structures. In near-field optics, however, the diffraction limit does not apply, which in principal allows for tighter focussing. In this contribution, a flexible approach for direct-write nanostructuring is presented. Dielectric micro-particles are positioned by Gaussian optical tweezers and irradiated by ultrafast laser pulses. The particles focus the pulses and enable surface structuring.
Created from Fastlane, Scopus look-up
Keywords: Direct-write; Nanostructuring; Optical trap; Ultrafast lasers

A simple laser beam characterization apparatus based on imaging - Bisti, F.; Alexeev, Ilya; Lanzetta, M.; Schmidt, Michael (Journal of Applied Research and Technology, 2021)
The development of an original low-cost hardware/software apparatus to optically control the laser beam and measure quality parameters by image analysis using a monochrome matrix sensor is described, along with experimental validation. Laser parameters, namely beam waist, divergence, Rayleigh range and M2, which are the most relevant in manufacturing operations (like optical measurement and laser processing), have been physically and mathematically characterized. Strategies for the apparatus size reduction are also presented, including the use of a prism to reduce by half the optical path, and a camera model to simulate the sensor resolution.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Apparatus design; Beam propagation analyzer; Image analysis; Laser quality

Beam guidance, focal position shifting and beam profile shaping in ultrashort pulsed laser materials processing - Bechtold, Peter; Zimmermann, Maik; Roth, Stephan; Alexeev, Ilya; Schmidt, Michael (Springer Verlag, 2016)
In ultrashort pulsed (USP) laser micro-processing several optical and optomechanical components are needed to enable the desired process. Besides the USP laser itself, systems to guide and focus the laser beam are mandatory in almost all applications. Furthermore beam profile shaping, e.g. the creation of top-hat or super-Gaussian beam profiles, results in beneficial effects for many applications, such as increased efficiency and superior quality. In this chapter an overview of both established and up-to-date technologies regarding beam guiding, focal position shifting and beam profile shaping will be presented. For beam guidance and focal position shifting comparable key parameters will be stated to enable easy comparability. As an outlook on probable future applications, both temporal and spatial polarization profile shaping will be presented.
CRIS-Team Scopus Importer:2023-03-07

Characterization of Shear Strength and Bonding Energy of Laser Produced Welding Seams in Glass - Alexeev, Ilya; Cvecek, Kristian; Schmidt, Christian; Miyamoto, Isamu; Frick, Thomas; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2012)
energy absorption. In this method ultrashort laser pulses, at a wavelength transparent to the processing material, are tightly focused onto the common interface of two glass pieces and absorbed via nonlinear interaction mechanisms, such as multi photon absorption. In this work we present recent results on the measurements of the shear strength and bonding energy for a number of laser welded soda-lime glass samples produces under different experimental conditions. We demonstrate that the shear strength and the bonding energy are affected differently by the processing parameters and present a qualitative explanation of the observed results. DOI:10.2961/jlmn.2012.03.0009
Keywords: Ultrafast material processing; glass welding; multiphoton processes

Defect formation in glass welding by means of ultra short laser pulses - Cvecek, Kristian; Alexeev, Ilya; Miyamoto, Isamu; Schmidt, Michael (Elsevier B.V., 2010)
Keywords: Glass and other amorphous materials; Laser materials processing; Glass welding; Ultrafast lasers; welding

Determination of laser beam focus position based on secondary speckles pattern analysis - Alexeev, Ilya; Wu, Ji; Karg, Michael; Zalevsky, Zeev; Schmidt, Michael (Applied Optics, 2017)
Proper positioning of a laser beam focus is a universal problem for various applications that does not have a universal solution. Quite often the taken approach relies on some sort of a calibration and temporal stability of the laser and the optical train. While such an approach can be suitable for a large number of applications its applicability becomes limited in the cases where the laser beam properties uncontrollably change with time. The latter can occur due to the thermal effects, for example. In those cases, the laser focus positioning method should include direct analysis of the laser beam properties. In this contribution we present a simple optical method based on the secondary speckles pattern analysis suitable for determination of the absolute focal spot position. The method does not require any a priori knowledge of the laser beam properties and is suitable for various diffuse or partially diffuse surfaces of interes
Keywords: Linear and nonlinear light scattering from surfaces; Speckle; Height measurements; Laser beam characterization

Determination of the effective refractive index of nanoparticulate ITO layers - Baum, Marcus; Alexeev, Ilya; Latzel, Michael; Christiansen, Silke; Schmidt, Michael (Optics Express, 2013)
Nanoparticles of transparent conducting oxides, such as indium tin oxide, can be used in printing techniques to generate functional layers for various optoelectronic devices. Since these deposition methods do not create fully consolidated films, the optical properties of such layers are expected to be notably different from those of the bulk material and should be characterized on their own. In this work we present a way to measure the effective refractive index of a particulate ITO layer by refraction of light. The obtained data points are used to identify an accurate layer model for spectroscopic ellipsometry. In this way the complex refractive index of the particle layer is determined in a wide spectral range from ultra violet to near infrared.
Keywords: ITO; refractive index; effective; ellipsometry

Direct Waveguide Writing with High Energy High Repetition Rate Picosecond Laser Pulses - Alexeev, Ilya; Cvecek, Kristian; Genser, Jan; Schmidt, Michael (Elsevier BV, 2012)
Direct femtosecond pulse laser waveguide writing based on laser induced localized modification of the refractive index of bulk glass can be a versatile fabrication method for many micro applications. Although the method's potentials have been realized its application is still rather limited, either due to the slow writing speeds caused by low laser pulse repetition rates of amplified systems or due to the shallow structuring depths restricted by low pulse energies of nonamplified lasers. In this work we investigate the direct waveguide writing process using a picosecond laser that allows fast and deep waveguide writing due to high pulse energies available at high pulse repetition frequencies. (C) 2012 Published by Elsevier B. V. Selection and/or review under responsibility of Bayerisches Laserzentrum GmbH
Keywords: direct waveguide writing; ultrafast micromachining

Efficient laser induced consolidation of nanoparticulate ZnO thin films with reduced thermal budget - Baum, Marcus; Polster, Sebastian; Jank, Michael; Alexeev, Ilya; Frey, Lothar; Schmidt, Michael (Applied Physics A-Materials Science & Processing, 2012)
Layers of ZnO nanoparticles with thicknesses of about 40 nm were prepared on Si substrates. It was shown that UV laser irradiation is suitable for consolidation and significant densification of the ZnO particle layers under ambient conditions. Both experiments and simulations show that an underlying SiO 2 particle layer has a beneficial effect in inhibiting heat transfer towards the substrate and thus enables the application of temperature-sensitive carrier substrates like polymer foils despite the extremely high melting temperature of ZnO. © 2012 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.LEB.effici
Keywords: ZnO; nanoparticle; laser; simulation; thin film; layer

Exploring the depth range for three-dimensional laser machining with aberration correction - Salter, P. S.; Baum, Marcus; Alexeev, Ilya; Schmidt, Michael; Booth, M. J. (Optics Express, 2014)
The spherical aberration generated when focusing from air into another medium limits the depth at which ultrafast laser machining can be accurately maintained. We investigate how the depth range may be extended using aberration correction via a liquid crystal spatial light modulator (SLM), in both single point and parallel multi-point fabrication in fused silica. At a moderate numerical aperture (NA = 0.5), high fidelity fabrication with a significant level of parallelisation is demonstrated at the working distance of the objective lens, corresponding to a depth in the glass of 2.4 mm. With a higher numerical aperture (NA = 0.75) objective lens, single point fabrication is demonstrated to a depth of 1 mm utilising the full NA, and deeper with reduced NA, while maintaining high repeatability. We present a complementary theoretical model that enables prediction of the effectiveness of SLM based correction for different aberration magnitudes. © 2014 Optical Society of America.
Created from Fastlane, Scopus look-up

Fabrication and Application of Phase only Holograms for High Power Laser Beam Shaping - Alexeev, Ilya; Brehm, Eric; Nendel, Florian; Strauß, Johannes; Baum, Marcus; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2016)
Fabrication of phase only holograms via spatially selective ablation of an ITO nanoparticulate layer coated on an optical quality transparent substrate appears to be very attractive due to the simplicity and flexibility of this approach. A pre-calculated binary pattern can be directly written on such a layer in order to produce a desired intensity distribution in the focal plane of a focusing lens. In this contribution we analyze the performance of the fabricated holograms and their suitability for high power beam shaping as well as propose a way to improve the diffraction efficiency of such structures by transitioning from a single to multi-layer holograms.
Keywords: phase only holograms; ultrafast ablation; ITO nanoparticles; beam shaping

Focus Alignment Method for Laser Manufacturing at Sub-micron Positional Accuracy - Strauß, Johannes; Cvecek, Kristian; Gröschl, Andreas Christian; Alexeev, Ilya; Schmidt, Michael (Physics Procedia, 2012)
Accurate positioning of a sample is one of the major challenges in the laser micro manufacturing – especially if the requirements on tolerances are high as in ultrafast laser micromachining. There are a number of methods that allow detection of the surface position, however only few of them use the beam of the processing laser as a basis for the measurement. These methods have an advantage that any changes in the structuring beam will be inherently accommodated for. This work describes a direct contact free method to accurately determine the surface position with respect to the structuring beam focal plane. The method makes alignment of unique samples precise and time efficient due to ease of automation and provides a reproducibility of surface detection of less than 1 μm.
Keywords: sample alignment; laser focus positioning; varying sample positioning

Friction Adjustment within Dry Deep Drawing by Locally Laser Textured Tool Surfaces - Häfner, Tom; Heberle, Johannes; Dobler, Michael; Gränitz, Michael; Alexeev, Ilya; Schmidt, Michael (Key Engineering Materials, 2015)
In deep drawing processes sustainability can be increased and processing steps can be omitted by abolishing any lubricants. Tailored tools with locally textured surfaces offer a possibility to compensate higher strains caused by the changed tribological system. Ultrashort pulsed laser machining is an advantageous approach to generate surface features. Thus, very hard and brittle materials can be processed inducing negligible heat affected zones so that the surrounding tool material keeps its initial properties. The material-dependent process parameters for efficient picosecond laser structuring are applied. The effects of features with single feature sizes in the range of 100 µm to 500 µm on friction of the tribological pairing are presented. The dependencies of the friction coefficient on the properties of the micro features - the geometry, the shape, the density and the orientation - are investigated by using a ring-on-disc-tribometer. The ring representing the tool is made out of the cold work steel 1.2379. The zinc-coated deep-drawing steel DC04 is used as disc respectively workpiece material. During the ring-on-disc-tests a constant contact pressure of 2.1 MPa and a mean sliding velocity of 100 mm/s are applied. To obtain the significant influences of micro features on friction, screening tests by varying the parameters according to the Shainin method are carried out. Because of the stochastically occurring high wear observed in reference experiments a changed methodology of ring-on-disc-tests is proposed. Applying this method the effects of textured ring surfaces on friction coefficient of steel-zinc-sliding are evaluated and compared to untextured rings. The latter are tested non-lubricated as well as with lubrication. The screening tests show that the feature orientation is the significant parameter influencing the friction. Selecting this parameter together with the feature density the friction coefficient can be adjusted with regard to untextured surfaces.
Keywords: Tribology; laser micro machining

Friction adjustment within dry deep drawing by locally laser textured tool surfaces - Häfner, Tom; Heberle, Johannes; Dobler, Michael; Gränitz, Michael; Alexeev, Ilya; Schmidt, Michael (Key Engineering Materials, 2015)
In deep drawing processes sustainability can be increased and processing steps can be omitted by abolishing any lubricants. Tailored tools with locally textured surfaces offer a possibility to compensate higher strains caused by the changed tribological system. Ultrashort pulsed laser machining is an advantageous approach to generate surface features. Thus, very hard and brittle materials can be processed inducing negligible heat affected zones so that the surrounding tool material keeps its initial properties. The material-dependent process parameters for efficient picosecond laser structuring are applied. The effects of features with single feature sizes in the range of 100 μm to 500 μm on friction of the tribological pairing are presented. The dependencies of the friction coefficient on the properties of the micro features-the geometry, the shape, the density and the orientation-Are investigated by using a ring-on-disc-tribometer. The ring representing the tool is made out of the cold work steel 1.2379. The zinc-coated deep-drawing steel DC04 is used as disc respectively workpiece material. During the ring-on-disc-tests a constant contact pressure of 2.1 MPa and a mean sliding velocity of 100 mm/s are applied. To obtain the significant influences of micro features on friction, screening tests by varying the parameters according to the Shainin method are carried out. Because of the stochastically occurring high wear observed in reference experiments a changed methodology of ring-on-disc-tests is proposed. Applying this method the effects of textured ring surfaces on friction coefficient of steel-zincsliding are evaluated and compared to untextured rings. The latter are tested non-lubricated as well as with lubrication. The screening tests show that the feature orientation is the significant parameter influencing the friction. Selecting this parameter together with the feature density the friction coefficient can be adjusted with regard to untextured surfaces.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Laser micro machining; Shainin; Tribology

Generation of phase-only holograms by laser ablation of nanoparticulate ITO layers - Baum, Marcus; Strauß, Johannes; Grüßel, Felix; Alexeev, Ilya; Schmidt, Michael (Journal of Optics, 2014)
Phase holograms offer great potential e.g. for laser beam shaping and imaging applications. However, the generation of these structures typically requires multi-step processes which tend to be time-consuming and expensive, especially if high-quality structures are required. In this work we demonstrate a flexible and inexpensive method which allows for the production of binary phase-only holograms by laser ablation of ITO nanoparticle layers. Since these layers are ablated free of residues, accurately defined phase shifts can be achieved. While arbitrarily shaped structures can be generated, the ITO layer thickness can be adjusted in order to freely tune the phase shift for the desired wavelength. In the diffraction patterns generated by the holograms we observed an excellent zero order suppression.
Keywords: hologram; binary; ITO; thin film; laser; ablation; nanoparticle

Generation of transparent conductive electrodes by laser consolidation of LIFT printed ITO nanoparticle layers - Baum, Marcus; Kim, Heungsoo; Alexeev, Ilya; Piqué, Alberto; Schmidt, Michael (Applied Physics A-Materials Science & Processing, 2013)
Indium tin oxide (ITO) is one of the few materials available that display a high transparency in the visible wavelength region and at the same time can conduct electrical currents. Thus it is widespread in many optoelectronic applications such as displays or solar cells. Layers of this material are commonly deposited by vacuum deposition methods which are not compatible with inexpensive production methods such as roll-to-roll processing or printed electronics in general. In this work, we demonstrate the generation of arbitrarily shaped ITO layers by laser induced forward transfer of ITO nanoparticles. The transferred particle ink volumes range in the sub picoliter regime. Feature sizes as small as 20 μm are produced without any outward flow or “coffee-stain” effects. Furthermore, the feasibility of excimer laser consolidation of these nanoparticulate layers in ambient air for the generation of dense ITO films is shown. Conductivities of over 4000 Ω−1 m−1 were achieved. The presented methods are a promising alternative for the generation of transparent conducting layers for the inexpensive production of optoelectronics.
Keywords: ITO; nanoparticle; Laser; LIFT; conductive; layer

High Speed Pump-Probe Apparatus for Observation of Transitional Effects in Ultrafast Laser Micromachining Processes - Alexeev, Ilya; Heberle, Johannes; Cvecek, Kristian; Nagulin, Konstantin; Schmidt, Michael (Micromachines, 2015)
A pump-probe experimental approach has been shown to be a very efficient tool for the observation and analysis of various laser matter interaction effects. In those setups, synchronized laser pulses are used to create an event (pump) and to simultaneously observe it (probe). In general, the physical effects that can be investigated with such an apparatus are restricted by the temporal resolution of the probe pulse and the observation window. The latter can be greatly extended by adjusting the pump-probe time delay under the assumption that the interaction process remains fairly reproducible. Unfortunately, this assumption becomes invalid in the case of high-repetition-rate ultrafast laser material processing, where the irradiation history strongly affects the ongoing interaction process. In this contribution, the authors present an extension of the pump-probe setup that allows to investigate transitional and dynamic effects present during ultrafast laser machining performed at high pulse repetition frequencies.
Keywords: imaging ultrafast phenomena; ultrafast laser glass processing; high-speed imaging

Konfokale Bestimmung der Fokuslage und Kalibriermethodiken entsprechender Systeme - Strauß, Johannes; Alexeev, Ilya; Cvecek, Kristian; Schmidt, Michael (Laser in der Elektronikproduktion & Feinwerktechnik, 2014)
Bei der Mikromaterialbearbeitung mit Ultrakurzpulslasern hat die absolute Bestimmung der Fokuslage zu der Werkstückoberfläche einen großen Einfluss auf das Bearbeitungsergebnis. In dieser Veröffentlichung wird demonstriert wie die von der Werkstückoberfläche reflektierte Laserstrahlung des Bearbeitungslasers mit einem konfokalem Messsystem ausgewertet wird, um so eine relative Positionsbestimmung mit 1/10 der Rayleighlänge durchzuführen. Des Weiteren wird gezeigt wie dieses Messsystem durch die höhere Harmonische, welche an der Oberfläche von Werkstoffen wie Glas erzeugt wird, kalibriert wird und somit eine absolute Positionsbestimmung des Bearbeitungsfokus zur Werkstückoberfläche erreicht wird.
Keywords: Schlagworte: Ultrakurzpulslaser; Mikromaterialbearbeitung; Bestimmung der absoluten Fokuslage; höhere Harmonische an dielektrischen Grenzflächen

Laser focus positioning method with submicrometer accuracy - Alexeev, Ilya; Strauß, Johannes; Gröschl, Andreas Christian; Cvecek, Kristian; Schmidt, Michael (Applied Optics, 2013)
Accurate positioning of a sample is one of the primary challenges in laser micromanufacturing. There are a number of methods that allow detection of the surface position; however, only a few of them use the beam of the processing laser as a basis for the measurement. Those methods have an advantage that any changes in the processing laser beam can be inherently accommodated. This work describes a direct, contact-free method to accurately determine workpiece position with respect to the structuring laser beam focal plane based on nonlinear harmonic generation. The method makes workpiece alignment precise and time efficient due to ease of automation and provides the repeatability and accuracy of the surface detection of less than 1 μm.
Keywords: 120.2830; 190.1900; 190.4350; 320.0320

Laser melting of nanoparticulate transparent conductive oxide thin films - Baum, Marcus; Polster, Sebastian; Jank, Michael; Alexeev, Ilya; Frey, Lothar; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
Layers of ZnO nanoparticles with thicknesses of about 40 nm were prepared on silicon sub-strates. The layers were irradiated by single pulses of a 248 nm excimer laser, which proofed suita-ble for consolidation and significant densification of the particle layers under ambient conditions. Experiments as well as simulations have confirmed that the application of a SiO2 particle layer be-tween the substrate and the ZnO particle layer can be used to hamper heat transfer towards the sub-strate. Thusthe ZnO layer can be thermally insulated from the substrate while heating the ZnO up to its extremelyhigh melting point. Consequently, such a layer stack could enable the application of consolidated particle layers on temperature-sensitive carrier substrates such as polymer foils which are to be used in low-cost mass production of devices like displays or solar cells.
UnivIS-Import:2015-03-09:Pub.2013.tech.IE.LEB.laserm
Keywords: Conducting layers; Laser melting; Nanoparticles; Transparent; ZnO

Laser Treatment of ITO and ZnO Nanoparticles for the Production of Thin Conducting Layers on Transparent Substrates - Baum, Marcus; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2011)
Layers of ITO nanoparticles were deposited on soda-lime substrates by spincoating in order to pro-duce conductive transparent electrodes. Different lasers in the UV and mid infrared wavelength re-gion were used for post deposition treatment of the layers to remove stabilizing agents contained in the layers to enhance particle-particle contact and significantly increase conductivities. Irradiation with lasers in the infrared region showed good results in terms of stabilizer removal without unde-sired oxidizing effects to the particle layer. Conductivities of up to 120 S/cm were achieved which is comparable to layer treatment by annealing and a subsequent chemical reducing step.
Keywords: ITO; ZnO; Laser; layer; conducting; transparent

Microsphere near-field nanostructuring using picosecond pulses - Leitz, Karl-Heinz; Quentin, Ulf-Hermann; Hornung, Benjamin; Otto, Andreas; Alexeev, Ilya; Schmidt, Michael (Physics Procedia, 2010)
In laser material processing the use of nonlinear multi-photon and near-field effects allows to produce nanostructures smaller than the wavelength of the processing laser. In the near-field of small particles locally restricted field enhancements occur, allowing a focusing of pulsed laser radiation far beyond the diffraction limit. In this contribution a basic study of near-field and beam-matter interaction phenomena in microsphere near-field nanostructuring using picosecond laser pulses shall be presented.
Created from Fastlane, Scopus look-up
Keywords: Laser based nanostructuring; Microsphere near-field enhancement; Ultrafast laser material processing

Multiphoton polymerization using optical trap assisted nanopatterning - Leitz, Karl-Heinz; Tsai, Yu-Cheng; Flad, Florian; Schäffer, Eike; Quentin, Ulf-Hermann; Alexeev, Ilya; Fardel, Romain; Arnold, Craig B.; Schmidt, Michael (Applied Physics Letters, 2013)
In this letter, we show the combination of multiphoton polymerization and optical trap assisted nanopatterning (OTAN) for the additive manufacturing of structures with nanometer resolution. User-defined patterns of polymer nanostructures are deposited on a glass substrate by a 3.5 mu m polystyrene sphere focusing IR femtosecond laser pulses, showing minimum feature sizes of lambda/10. Feature size depends on the applied laser fluence and the bead surface spacing. A finite element model describes the intensity enhancement in the microbead focus. The results presented suggest that OTAN in combination with multiphoton processing is a viable technique for additive nanomanufacturing with sub-diffraction-limited resolution. (C) 2013 AIP Publishing LLC.

New approaches in teaching laser engineering classes - modeling and building up a laser - Alexeev, Ilya; Pflaum, Christoph; Schmidt, Michael (SPIE-INT SOC OPTICAL ENGINEERING, PO BOX 10, BELLINGHAM, WA 98227-0010 USA, 2017)
We present a simulation tool to model performance of a bulk solid state laser and propose several ways how this tool can be used to enhance educational experience of the student studying laser technology. In one of the possible approaches, the ASLD software can complement available educational laser kits to provide the students with more universal practical training. In the second approach, which is the primary focus of this contribution, the ASLD software can be used as a development tool that allows students to verify their understanding of the subject as well as to propose and verify their own design ideas. The software can be extremely helpful if an experimantal setup has to be built from already present optical components in order to reduce the cost of training or if specific design objectives have to be attained.
Keywords: Laser resonator modeling; ASLD software; ultrafast lasers

Numerical simulation of short laser pulse amplification - Springer, Ramon; Alexeev, Ilya; Heberle, Johannes; Pflaum, Christoph (Journal of the Optical Society of America B-Optical Physics, 2019)
Within this work, the numerical solution of the photon transport equation for pulse amplification is presented. Several discretization schemes are introduced that enable the calculation of the coupling between the transport equation and population inversion. It is demonstrated that the presented discretization schemes are convergent with respect to the analytic Frantz-Nodvik solution. Specifically, the application of a prediction-correction approach based on Heun's method leads to an improvement in accuracy compared to the pure explicit approach. Finally, novel discretization schemes are applied to simulate different regenerative amplifiers based on Ti:Sapphire and Ho:YAG. Moreover, bifurcation of the Ho:YAG system is analyzed, which results in the determination of stable operating regimes for pulsed amplification. (C) 2019 Optical Society of America
CRIS-Team WoS Importer:2019-03-15

Optical trap assisted laser nanostructuring in the near-field of microparticles - Quentin, Ulf-Hermann; Leitz, Karl-Heinz; Deichmann, Lutz; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Applications, 2012)
Particle based near-field nanostructuring is an excellent possibility to overcome the optical diffraction limit in laser based material processing. In the near-field of microspheres which are irradiated with pulsed laser radiation, it is possible to generate nanoholes with diameters below 100 nm using a laser wavelength of 800 nm. To improve this approach, it is possible to position the microparticles with an optical trap to generate arbitrary structure geometries. In this paper, the authors describe the basic principle of optical trap assisted nanostructuring and present simulational and experimental results demonstrating the potential of this innovative nanoscale optical material processing technology. © 2012 Laser Institute of America.
Created from Fastlane, Scopus look-up
Keywords: direct-write; nanostructuring; near-field; optical trap; optical tweezers; ultrafast lasers

Optical Trap Assisted Nanopatterning: Process Parallelisation and Dynamic Structure Generation - Strauß, Johannes; Baum, Marcus; Alexeev, Ilya; Schmidt, Michael (International Congress on Laser Advanced Materials Processing, 2015)
In this publication we present a novel setup for Optical Trap Assisted Nanopatterning (OTAN) technology. The setup allows for parallelization and thus for higher throughput in this inventive and flexible direct-nanopatterning technology. In addition we present first results of parallel nanoscale structuring. We determine the stiffness of optical traps and compare the result to previous results of single OTAN. Furthermore we estimate the increase of throughput for the parallelized approach with respect to the conventional system.

Optical Trap Assisted Nanopatterning: Process Parallelization and Dynamic Structure Generation - Strauß, Johannes; Baum, Marcus; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2017)
In this publication we present a novel setup for the Optical Trap Assisted Nanopatterning (OTAN) technology. The setup allows process parallelization and thus higher throughput in this inventive and flexible direct-nanopatterning technology. We have determined the stiffness of the optical traps and compared the obtained result with the single beam OTAN parameters. Furthermore we estimate the increase in throughput for the parallelized approach in comparison to the conventional syst
Keywords: nanostructuring; direct-write; optical trapping; ultrafast laser processing; holographic laser beam shaping

Optical trap assisted sub diffraction limited laser structuring - Alexeev, Ilya; Quentin, Ulf-Hermann; Leitz, Karl-Heinz; Strauß, Johannes; Baum, Marcus; Stelzle, Florian; Schmidt, Michael (Walter de Gruyter GmbH & Co KG, 2015)
The ability to structure surfaces on a submicron scale is becoming increasingly important for a broad range of technical and biological applications. Such structures can be produced via irradiating micron sized transparent particles placed over a substrate of interest with ultrafast laser pulses. To enhance the structuring flexibility of this method particles can be optically trapped and spatially manipulated relative to the structured surface in order to achieve arbitrary patterns. In this contribution the authors describe the principle of optical trap assisted nanostructuring and present simulated and experimental results demonstrating the potential and limitations of this innovative nanoscale optical material processing technology.

Optical trap kits: Issues to be aware of - Alexeev, Ilya; Quentin, Ulf-Hermann; Leitz, Karl-Heinz; Schmidt, Michael (European Journal of Physics, 2012)
An inexpensive and robust optical trap system can be built from off-the-shelf optical and opto-mechanical components or acquired as a kit to be assembled in a laboratory. The primary advantages of such a trap, besides being significantly more affordable, are its flexibility, and ease of modification and upgrade. In this paper, we consider several important issues to be addressed during development and application of a kit system. We numerically examine the performance of trapping systems equipped with oil and water immersion focusing objectives. We also investigate the effect of trapping laser beam quality on optical tweezing. © 2012 IOP Publishing Ltd.

Picosecond laser ablation behavior of IOL-materials - Heberle, Johannes; Klämpfl, Florian; Quentin, Ulf-Hermann; Alexeev, Ilya; Schmidt, Michael (Proceedings of the 7th Russian Bavarian Conference on Biomedical Engineering, 2011)
Multifocal phakic intraocular lenses are an attractive method to correct presbyopia. The manufacturing of such lenses by picosecond laser structuring is a very promising approach. In this paper we present our results of the ablation behavior of current intraocular lens materials regarding ablation threshold and ablation rate.
Keywords: ultrafast laser; polymer; structuring; multifocal intraocular lens

Positioning accuracy in optical trap assisted nanostructuring - Quentin, Ulf-Hermann; Leitz, Karl-Heinz; Paulus, Jan; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
The well-known optical diffraction limit prevents laser radiation from being focused to arbitrary small spots. Utilizing spherical micro-particles as near-field lenses provides an easy and robust way to overcome this limitation and to generate nanoscale surface structures. To achieve this, microspheres are positioned and translated with an optical trap and then used to focus pulsed laser radiation. The paper at hand presents the factors which influence the positioning accuracy in optical trap assisted nanostructuring. Theoretical considerations are backed up with experimentally obtained values of the surface structure accuracy in dependence of optical trap stiffness and particle position.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Direct-write; Nanostructuring; Optical trap; Ultrafast lasers

Practical Aspects of Surface Generated Third Harmonic for Highly Precise Beam-workpiece Alignment - Cvecek, Kristian; Strauß, Johannes; Alexeev, Ilya; Miyamoto, Isamu; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
Precise beam-workpiece alignment is highly important in laser processing. Though many methods exist for this task few allow high-precision measurements using the processing laser itself. One such method detects the laser’s backreflection from the workpiece’s surface using a confocal setup and yields ideally an accuracy of about 10% of the Rayleigh length of the focused beam. Nevertheless, under certain conditions the accuracy of this method may suffer from a mismatch of beam divergences between laser and confocal detection optics. This becomes important when transparent materials are processed in three dimensions using optics with very high numerical apertures or if expensive materials or samples have to be processed where any misalignment would be costly. A possible solution to this is surface based third harmonic generation that allows for absolute surface detection while having the same accuracy as the confocal method. However, this method requires a complex setup while exhibiting low conversion efficiency. Both reasons make a proper alignment of this measurement scheme difficult. Herein we present results showing a clear conversion efficiency dependence on the reflection coefficient of the generating interface for a number of material combinations. This makes the selection of suitable materials more straightforward and reduces the alignment effort. The highest conversion efficiency was achieved for air/silicon which exhibits the highest reflection coefficient of the investigated materials.
Keywords: Laser materials processing; height measurements; diagnostic applications of nonlinear optics; nonlinear optics at surfaces; ultrafast optics

Process investigations of optical trap assisted direct-write microsphere near-field nanostructuring - Leitz, Karl-Heinz; Quentin, Ulf-Hermann; Alexeev, Ilya; Schmidt, Michael (CIRP Annals - Manufacturing Technology, 2012)
Keywords: Laser; Microsphere near-field focusing; Nano manufacturing

Simulation of energy buildups in solid-state regenerative amplifiers for 2-μm emitting lasers - Springer, Ramon; Alexeev, Ilya; Heberle, Johannes; Pflaum, Christoph (SPIE Photonics West, 2018)

Simulation of energy buildups in solid-state regenerative amplifiers for 2-μm emitting lasers - Springer, Ramon; Alexeev, Ilya; Heberle, Johannes; Pflaum, Christoph (SPIE Photonics West Proceedings, 2018)
Keywords: Solid-state; Regenerative Amplifier; Upconversion; Bifurcation; Numerical Simulation; Ho:YAG

Structural analysis of direct laser written waveguides - Salter, P. S.; Jesacher, Alexander; Huang, L.; Liu, X.; Baum, Marcus; Alexeev, Ilya; Schmidt, Michael; Booth, M. J. (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
We perform structural characterisation of direct laser write (DLW) waveguides. Quantitative phase microscopy, based on solution of the transfer of intensity equation, is used to measure the cumulative refractive index change through a waveguide perpendicular to its axis. Results are compared with interferometry, cross-sectional measurements using third harmonic microscopy, and analysis of the near-field image of the mode propagating in the waveguide. We show that in many situations, notably in the presence of depth dependent spherical aberrations, the cross-section for DLW waveguides may not be assumed symmetric about the waveguide axis. This is particularly important when fabricating at depths greater than 2 mm in fused silica. Therefore additional measurements are required to fully characterise the refractive index profile. © 2014 SPIE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Laser fabrication; Microscopy; Photonics; Waveguides

The influence of laser induced consolidation on the ablation threshold of nanoparticulate ITO-layers - Mikschl, Florian; Baum, Marcus; Heberle, Johannes; Alexeev, Ilya; Schmidt, Michael (Physics Procedia, 2014)
Indium tin oxide (ITO) is one of the few materials, which combines optical transparency in the wavelength range of visible light and electrical conductivity. It offers a wide range of applications in the field of optoelectronic devices such as solar cells or displays. To the present day, ITO is commonly deposited in a vacuum environment. Deposition under vacuum atmosphere is a cost-intensive process and not compatible with modern manufacturing techniques, like roll-to-roll processing. To overcome this limitation we propose the generation of ITO layers by deposition of ITO nanoparticles under atmospheric conditions. For the generation of functional devices structured layers are required. The exact damage threshold of nanoparticulate ITO layers is essential to minimize influence of the structuring process on the substrate. In our measurements we used three different substrates, spin coated layers, annealed layers and consolidated layers.
Keywords: ITO; Structuring; Damage Threshold; ultra-short pulse laser

Toner-print removal from paper by long and ultrashort pulsed lasers - Leal-Ayala, David Ricardo; Allwood, J. M.; Schmidt, Michael; Alexeev, Ilya (Proceedings of the Royal Society A-Mathematical Physical and Engineering Sciences, 2012)
Toner-print removal from paper would allow paper to be re-used instead of being recycled, incinerated or disposed of in landfill. This could significantly reduce the environmental impact of paper production and use. Previous work on the subject has explored the applicability of ultraviolet, visible and infrared (IR) lasers under nanosecond pulses for toner removal. This article expands on this work by testing a wider range of ultrafast and long-pulsed lasers. Results from 10 distinct laser set-ups are used to propose an operating window for the toner-removal process. Colour analysis under the L*a *b* colour space, scanning electron microscope examination and attenuated total reflectance-Fourier transform IR spectroscopy measurements of the outcome show that, with the right laser, it is possible to remove toner from paper to enable its re-use. Theoretical models to predict the laser ablation of toner are discussed, and, while imperfect, provide sufficient evidence to support a physical explanation of toner ablation. © 2012 The Royal Society.
Created from Fastlane, Scopus look-up
Keywords: Laser ablation; Material efficiency; Paper recycling; Reduction of paper demand; Toner print

Ultrafast Laser Surface Structuring of Intraocular Lens Polymers - Heberle, Johannes; Klämpfl, Florian; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
Ultrafast laser material processing is an attractive approach for surface structuring of medical polymers used for intraocular lenses. To achieve best results in terms of efficiency and quality, the wavelength and pulse energy dependence on the ablation behavior of such materials has to be studied. Ablation thresholds have been determined for a polymer with different dyes which is used for intraocular lens (IOL) manufacturing. Furthermore, the ablation efficiency, achievable precision and surface roughness have been quantified to optimize the parameters for an efficient intraocular lens manufacturing process by surface microstructuring.
Keywords: Ablation; Intraocular lens; Picosecond; Polymer; Structuring; Surface roughness.; Ultrashort pulses; Wavelength dependent

Ultrafast microsphere near-field nanostructuring - Leitz, Karl-Heinz; Quentin, Ulf-Hermann; Hornung, B.; Otto, Andreas; Alexeev, Ilya; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2011)
Due to the steadily advancing miniaturization in all fields of technology nanostructuring becomes increasingly important. Whereas the classical lithographic nanostructuring suffers from both high costs and low flexibility, for many applications in biomedicine and technology laser based nanostructuring approaches, where near-field effects allow a sub-diffraction limited laser focusing, are on the rise. In combination with ultrashort pulsed laser sources, that allow the utilization of non-linear multi-photon absorption effects, a flexible, low-cost laser based nanostructuring with sub-wavelength resolution becomes possible. Among various near-field nanostructuring approaches the microsphere based techniques, which use small microbead particles of the size of the wavelength for a sub-diffraction limited focusing of pulsed laser radiation, are the most promising. Compared to the tip or aperture based techniques this approach is very robust and can be applied both for a large-scale production of periodic arrays of nanostructures and in combination with optical trapping also for a direct-write. Size and shape of the features produced by microsphere near-field nanostructuring strongly depend on the respective processing parameters. In this contribution a basic study of the influence of processing parameters on the microsphere near-field nanostructuring with nano-, pico- and femtosecond laser pulses will be presented. The experimental and numerical results with dielectric and metal nanoparticles on semiconductor and dielectric substrates show the influence of particle size and material, substrate material, pulse duration, laser fluence, number of contributing laser pulses and polarization on the structuring process. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).
Created from Fastlane, Scopus look-up
Keywords: microsphere near-field nanostructuring; multi-photon absorption; near-field effects; Ultrafast material processing

Ultrafast (picosecond) laser oscillator for educational use - Pflaum, Christoph; Alexeev, Ilya; Ugurlu, Asli Dilara; Seerdar, G (European Journal of Physics, 2016)
Here, we present a description of an inexpensive ultrafast self-starting passively mode-locked laser oscillator that can be constructed using widely available off-the-shelf optical components. Such a laser system can be used to teach students the principles of solid state laser engineering, demonstrate a number of nonlinear optical phenomena, and perform qualitative and quantitative comparisons between numerical laser modeling and experimental results.
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.c3sim.ultraf
Keywords: passive mode-locking; semiconductor saturable absorber; ultrafast laser

Ultrakurz-gepulstes Laserstrahlschneiden biokompatibler Kunststoffe - Heberle, Johannes; Klämpfl, Florian; Alexeev, Ilya; Schmidt, Michael (Tagungsband des 17. Seminars Laser in der Elektronikproduktion und Feinwerktechnik, 2014)
Materialabtrag mittels ultrakurz gepulster Laserstrahlung ist ein attraktiver Ansatz für verschiedene Anwendungen. Ein Beispiel hierfür ist die Herstellung von Intraokularlinsen (IOL), die aus biokompatiblen Polymeren bestehen und meist komplexe Formen der refraktiven Oberfläche sowie der Haptiken aufweisen. Im Gegensatz zu aktuell eingesetzten spanabhebenden Verfahren ermöglichen ultrakurz gepulste Laser eine kontaktlose, geometrisch flexiblere und signifikant schnellere Bearbeitung. Die Ausbildung von Wärmeeinflusszonen kann dabei durch geeignete Parameterwahl vermieden werden. Um die besten Ergebnisse hinsichtlich Qualität und Effizienz zu erzielen, werden daher Untersuchungen zum Abtragsverhalten bei unterschiedlichen Wellenlängen sowie unter Variation der relevanten Prozessparameter durchgeführt. Basierend auf den Ergebnissen wird ein Schneidprozess für die Kontur der IOL vorgestellt, der es ermöglicht, geometrisch komplexere Formen mit deutlich erhöhter Effizienz herzustellen. Hiefür wird das Prozessfenster, das eine zu den üblicherweise eingesetzten Verfahren vergleichbare Kantenqualität ermöglicht, sowie Parameterbereiche mit definierten Arten von Prozessfehlern präsentiert und theoretisch erläutert.
Keywords: Intraokularlinsen; biokompatibler Kunststoff; ultrakurze Laserpulse; Schneiden

Ultrashort Pulse Laser Cutting of Intraocular Lens Polymers - Heberle, Johannes; Klämpfl, Florian; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2014)
Material processing by ultra-short pulsed laser ablation is an attractive approach for various ap-plications. In this paper we present our studies on cutting of medical polymers used for intraocular lenses (IOL). To achieve best results the ablation characteristics and the ablation thresholds are identified for single and multiple irradiation of the lens material by picosecond pulses. The results are used for quantification of the incubation effect. Furthermore, cutting experiments are carried out and thereby different damage types can be observed. A process window is developed containing the regions of the respective types of damages and backed up by theoretical considerations.
Keywords: Ablation; Cutting; Incubation effect; Intraocular lens; Near infrared; Picosecond; Ultrafast laser; Ultrashort pulsed